Identity Negotiation of Chinese Students in Canada: A Study on Cosmopolitan Post-Graduation Settlement - Zhao, Yuxi (Université d'Ottawa / University of Ottawa, 2020)
This study focuses on the analysis of the acculturation of Chinese international students in Canada, with an emphasis on students’ post-graduation settlement in China, Canada or other countries. Chinese international students commonly experience a multilayered acculturative adjustment when they are challenged by a new culture. In this process, they develop an identity negotiation that impacts their settlement into a new country. This study mobilizes the model of acculturation and four notions of acculturation (assimilation, integration, marginalization and separation), to evaluate Chinese international students’ identity negotiation after the acculturation. This research uses 17 semi-structured interviews, to understand how participants’ identities were negotiated through their acculturative adjustment. The findings highlight the importance of career factors and family values in participants’ settlement decisions, while the balance between Chinese identity and Canadian identity has some impact on student’s migration plans.
Keywords: Identity negotiation; Cosmopolitanism; Acculturation; Semi-structured interview; International students